The Impact of Work Related Stress onto Quantity Surveyors’ Work Productivity in the Consultancy Firms in Klang Valley, Malaysia - Hurgobin, Jenita Devi; Chan, Siew Chong (2016)
The construction industry is a high-risk industry for work stress. Professional working groups such as Quantity Surveyors have to face stress on a daily basis which is a major challenge to their health and further lower their productivity. However this work related stress is being less highlighted in the Malaysian Consultancy firms whileas this working pressure may be one of the causes of anxiety and depression which if no action is further taken, may cause death. Transactional stress model designed by Cox and McKay is used to assess the implications of work stress onto work productivity range in accordance to on time completion of works, quality of works and satisfaction of works. Besides that, the main causes of stress are also compared and related possible solution are suggested in order to manage the work related stress. Questionaire with likert scales were given to respondents to rate the relevant stress factors, and the data was further analysed using Descriptive Analysis with Ranking of Average Value. Through this study, work related stress does have significance implication onto the QS work productivity based on analysis output of this model, especially the pressure of completion on time. Hence, related strategies should be proposed and implemented to ensure the progress of work are well under control not only within the QS work practice, but also in overall construction team.